Stages and Ways of Company’s Growth - Stravinskas, Jonas (Ekonomika, 2000)
There are analysis of company’s growth stages and evaluation of main problems, companies face growing up (those problems differ in different stages) in this article.Not growing company can not be of great vitality. New skills and professional development of managers is needed to encourage the growth of the company. That is one of the biggest problems Lithuanian companies so far.Analysis of company’s growth, referring on practice of foreign companies, let us review and evaluate the main ways which stimulate growth of the company.To sustain growth, the company must have a continues flow of initiatives. That is the main idea of the article. Assurance of supply of system by necessary growth resources can ensure realisation of new growth opportunities. There is a suggestion to use the method of “seven degrees of freedom”, created by consulting company MeKinscy&Co, for the managers seeking to use new opportunities and fresh options for growth pursuance. This method allow to uncover opportunities that might otherwise remain hidden.The aim of the article is to evaluate the problems and dangers that might appear while company’s growing, to analyse changes and solutions of the problems and present possibilities of avoiding of these threats.